The Effect of Service Quality and Atmosphere on Revisit Intention to Klewer Market a Social Economic - Muhammad Ilham Masyary; Darsono; Kurniawati Darmaningrum (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to determine the effect of service quality and atmosphere on the intention to revisit Klewer Market in Surakarta City amidst digital competition with the ease of online fahion purchases that have changed consumer behavior and decreased visits to physical markets. Methodology: This study used quantitative methods with 100 respondents who had visited in the last six months. Data collection techniques were conducted through surveys, while data analysis techniques used descriptive or inferential statistical analysis. All data were processed using SPSS version 25 software to ensure the accuracy of the test results. Main Findings: The results show that service quality and atmosphere have a significant partial and simultaneous effect on the intention to revisit. As a social space, traditional markets facilitate community interaction activities. Service quality and atmosphere that support these activities are crucial for the sustainability of this social institution. Novelty/Originality of this study: This study offers a new perspective by repositioning traditional markets not only as economic entities, but also as dynamic social spaces. Its novelty lies in the integration of service quality and atmosphere as stimulants for community social activities, which are key to the sustainability of social institutions amid modernisation.